(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed at identifying the cognitive achievement among football coaches in Jordan, as well as identifying the differences in the cognitive achievement in the physiology of physical effort among football coaches in Jordan in relation to the study variables (training experience, educational qualification, age, coach’s rank, coach’s academic specialization, coach’s training field, club’s class). The study sample consisted of 104 coaches working in professional football clubs, and in the first, the second and third classes in Jordan. The researchers used the descriptive approach due to is compatibility to the study nature and its objectives, and an achievement test was used as a tool for data collection, where the test included (30) questions in the physiology of physical effort. The data were statistically analyzed using means, standard deviations, percentages, skew coefficient, one-way analysis of variance, (t-test) for independent groups and Scheffe test for statistically significant dimensions. The results showed that the level of the cognitive outcome in the physiology of physical exertion among football coaches in Jordan was low, and that the level of the cognitive outcome in the physiology of physical effort among football coaches in Jordan was not affected by the variables of training experience, age, coach degree, training field and club class, while it was affected by the educational qualification, but they all remained at a low level. In light of the results, the study recommended the necessity of urging football coaches to pay attention to the cognitive aspects in the physiology of physical effort, developing them, and taking them into account when training players and planning sports programs.